MODEL OF GROWTH OF CULTURE STARTER IN CHEESE FERMENTATION - INSAN NURBAHAGIA (NIM : 10108101); Pembimbing : Dr. Nuning Nuraini,
Cheese is one of the main dairy products are formed by coagulation of milk by rennet (a digestion enzyme in the stomach of animals that producing milk). The various of Cheese products determined from the type of milk, method of coagulation, temperature, method of cutting, drying, heating, as well as the process of cheese ripening and preservation. Fermentation carried by bacteria that produce lactate fermentation of lactose. In this thesis, I will formulate a mathematical model of the growth of culture. This model use one type of bacteria, which is one of the main lactic acid bacteria, Lactococcus lactis. There are two kind model in this thesis, chemostat and batch culture models. Chemostat model is constructed based on the analysis compartment, during the legal action, and the balance period. This model uses equations Michaelis Menten or Monod equation. However, there are some weaknesses in this model, because this model is too simple and sometimes do not represent as results of a product ( lactic acid). Therefore, a second model was developed, Batch Culture. This model describe culture of model cells in a tank (bioreactor) with an initial medium that was not changed (medium only entered at the start of cultivation) by the addition of nutrients or substances nesting in the bioreactor.Batch Culture model is better than the chemostat models, because the model Batch Culture represents the results in the form of products Luedeking Piret model.